2016
DOI: 10.1099/jgv.0.000366
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale screening and characterization of enteroviruses and kobuviruses infecting pigs in Vietnam

Abstract: A recent survey of pigs in Dong Thap province, Vietnam identified a high frequency of enterovirus species G (EV-G) infection (144/198; 72.7 %). Amongst these was a plethora of EV-G types (EV-G1, EV-G6 and four new types EV-G8-EV-G11). To better characterize the genetic diversity of EV-G and investigate the possible existence of further circulating types, we performed a larger-scale study on 484 pig and 45 farm-bred boar faecal samples collected in 2012 and 2014, respectively. All samples from the previous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
34
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 42 publications
6
34
1
Order By: Relevance
“…Enteroviruses have been more generally linked to neurological disorders in pigs, although they are commonly found in feces as well 11,12,[32][33][34] . In a study from Vietnam, no significant correlation was found between diarrhea status and presence of enterovirus G in feces 35 . The involvement of both astro-and enteroviruses in the pathogenesis of enteric disorders might be questioned here, but cannot be completely ruled out.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Enteroviruses have been more generally linked to neurological disorders in pigs, although they are commonly found in feces as well 11,12,[32][33][34] . In a study from Vietnam, no significant correlation was found between diarrhea status and presence of enterovirus G in feces 35 . The involvement of both astro-and enteroviruses in the pathogenesis of enteric disorders might be questioned here, but cannot be completely ruled out.…”
Section: Discussionmentioning
confidence: 86%
“…However, the prevalence of kobuvirus has been widely described in pigs from several European countries (The Netherlands (16.7%), Slovakia (63.4%), Hungary (81.0%), Czech Republic (87.3%), Austria (46.2%), Italy (52.4%), Germany (54.5%) and Sweden (45.0%)), American countries (The United States (21.9%) and Brazil (53.0%)), African countries (Kenya (14.9%) and Uganda (15.5%)) and Asian countries (Thailand (99%), South Korea (52.1%) and Vietnam (29.3%)) [44][45][46][48][49][50][51][52][53] . In a small proportion of these studies, statistically significant associations between prevalence of kobuvirus and diarrhea in pigs were demonstrated, such as in Hungary (54.5% prevalence in healthy pigs vs 92.3% prevalence in diarrheic pigs), Spain (47.5% healthy vs 74.4% diarrheic), Brazil (41% vs 78.4%), Thailand (19.3% vs 84.5%) and Vietnam (27.6% to 40.9%) 35,45,46,52 . Indeed, it is difficult to make correlations between prevalence of the virus and diarrhea, as the pathogenicity of the virus could be largely influenced by other factors such as co-infections with other enteric viruses, microbiota and management factors.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, the prevalence of EV-G infections in Vietnam was up to 90 % in piglets and 40 % in pigs over 1 year of age [8,9], and the prevalence among Spanish swine herds at six farms ranged from 2 to 82 % [10]. A recent analysis found no difference in the prevalence of EV-G infection in pigs from Vietnam, with or without diarrhoea [8].…”
mentioning
confidence: 99%
“…The 14 currently available EV-G complete genomes from GenBank (with VP1-based genotypes: 1-6, 8-10) were identified from swine in the UK, Belgium, China, Hungary, Vietnam, South Korea and the USA [9,13,[27][28][29][30][31][32][33]. Currently, EV-G genotypes are classified solely by the VP1.…”
mentioning
confidence: 99%
“…EV-Gs are detected mainly in domestic pigs (EV-G1 to -4, -6, -8 to -15, and -17 to -19) (http://www.picornaviridae.com/enterovirus/ev-g/ev_g_seq.htm). Recent reports have shown that the virus can also be isolated from wild boars (EV-G4 and -16), small ruminants such as sheep (EV-G5 and -7), goats (EV-G20), and Sichuan takins from several countries in Europe, Asia, and the Americas (19,20,(27)(28)(29). In animals naturally infected with EV-G, neurological disorders, fertility disorders, diarrhea, and dermal lesions have been reported, although the mechanism of their pathogenesis remains unclear (30)(31)(32).…”
mentioning
confidence: 99%